Human health risk and food safety implications of microplastic consumption by fish from coastal waters of the eastern equatorial Atlantic Ocean. (March 2023) - Mahu, Edem; Datsomor, Wise Goodluck; Folorunsho, Regina; Fisayo, Jerome; Crane, Richard; Marchant, Robert; Montford, Judith; Boateng, Mario Charles; Edusei Oti, Maurice; Oguguah, Margret Ngozi; Gordon, Christopher
Abstract: We examined the gastro-intestinal tracts (guts) of 160 fish species obtained from Nigerian coastal waters for microplastics and estimated annual microplastic intake by adult human population in the region from the fish species. A total of 5744 microplastics were recovered from the fish species analyzed with an average of 39.65 ± 5.67 items/individual. Microbeads (43%) occurred in all guts assessed, followed by fragments (27%), burnt film (14%), thread (9%), fibers (4%), and pellets (3%). Most microplastics recovered were below 1000 μm with the least size being 85 μm. Based on the size classes estimated for this study, we argue based on literature that close to 15% (i.e., >100 μm) of the microplastics in the guts studied have the potential to translocate gut barriers of the fish species into muscles, where they get ingested by humans, and thereon get translocated to other human organ tissues. The estimated annual intake of microplastics from the consumption of whole fish by the adult population followed the trend; M. cephalus (178, 220) >  I. Africana (131, 670) >  P. senegalensis (115, 710) >  P. jubelini ( 109, 060) >  S. maderensis (101, 080) >  G. decadactylus (101, 346) > S. melanotheron (65, 170). Estimated annual intakes were generally higher for fish species with broad habitat and feeding preferences. Graphical abstract: Image 1 Highlights: Total of 5744 microplastics were detected in 160 fish species analyzed. A mean of 39.65 ± 5.67 microplastics obtained per fish gut analyzed. Mugil cephalus, an ominivorous, euryhaline benthopelagic fish had the highest number of microplastics. Microbeads, fragments and burnt films dominated microplastic counts. Polyethylene constituted the dominant polymer identified in the fish gut.